Did Inequalities in Mothers' and Children's Health and Well-Being in Japan Increase through the Pandemic? Evidence from Nationwide Surveys and Routinely Collected Data - Hajime Takeuchi; Yoichi Satoh; Shanti Raman; Nick Spencer (MDPI AG, 2024)
Marginalised families faced significant challenges during the COVID-19 pandemic. This study explores inequalities in Japanese mothers' and children's health and well-being and family economic stability before and during the pandemic. Data sources were as follows: nationwide surveys in 2019 and 2021 of families with children using medical institutions across Japan; infant mortality and adolescent suicide rates between 2018 and 2021 from publicly available sources. Outcomes by poor and non-poor families were compared for 2019 and 2021 using simple descriptive statistics. Poor mothers' part-time working increased from 41% to 61% and regular employment was reduced by two thirds. The well-being of poor mothers worsened from 39% to 55%. Employment opportunities and well-being did not change for non-poor mothers. School subsidies among poor families increased from 23% to 55%. The infant mortality rate (IMR) among unemployed families increased significantly from 12.9/1000 to 18.2/1000 between 2018 and 2021 compared with a decreasing overall IMR from 1.9/1000 to 1.7/1000. Suicide rates in 10-19-year-olds increased over the same period although no socio-economic indicators were available. Inequalities in mothers' and children's health and well-being indicators and family economics increased between 2019 to 2021 in Japan. This study cannot attribute causes but suggests a possible role of the pandemic.